Accurately Localizing Multiple Nanoparticles in a Multishelled Matrix Through Shell-to-Core Evolution for Maximizing Energy-Storage Capability - Li, Bo (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.